Розробка технології та порівняльний аналіз створення тривимірних моделей в середовищі сучасних САПР з урахуванням процесів формоутворення різанням - Тигарєв, В. М.; Тонконогий, В. М.; Вайсман, В. О.; Бабіч, Ю. І.; Салій, В. І. (Національний технічний університет "Харківський політехнічний інститут", 2019)
Наведено послідовність розвитку комп’ютерних технології по створенню моделі деталі з використанням різноманітних підходів. Розглянуто параметричне проектування, пряме моделювання, (без дерева побудови та жорстких зв’язків між конструктивними елементами), варіаційне моделювання. Подібні рішення застосовувалися виключно для 2D-ескізу і побудови зв'язків «зверху вниз» для складальних вузлів, які не охоплювали тривимірного моделювання. Ситуація змінилась з появою синхронної технології, яка змогла поширити варіаційний підхід до моделювання на весь ланцюжок проектування виробу. Тобто синхронна технологія дозволяє змінювати функціонал прямого моделювання безпосередньо в параметричному середовищі. Розроблено алгоритм створення тривимірної моделі деталі в синхронному середовищі. Розглянуто технологію створення тривимірної моделі деталі типу “Корпус” в синхронному середовищі проектування сучасної САПР Solid Edge. Докладно наведено особливість створення та редагування тривимірної моделі деталі та її елементів з урахуванням особливостей технологічних процесів формоутворення різанням. Проведено порівняльний аналіз проектування у синхронному та параметричному середовищах з поясненням переваг та недоліків.

A sequence over of development of computer is brought technologies on creation of model of detail with the use of various approaches. The self-reactance planning, direct design is considered, (without the tree of construction and hard connections between structural elements), variation design. Similar decisions were used exceptionally for to the 2d-sketch and constructions of connections "from top to bottom" for frame-clamping knots that did not embrace a three-dimensional design. A situation changed with appearance of synchronous technology, that was able to spread the variation going near a design on all chainlet of planning of good. It is synchronous technology allows to change the functional of direct design directly in a self-reactance environment. The algorithm of creation of three-dimensional model of detail is worked out in a synchronous environment. In an algorithm thoroughly to consider all stages of creation of three-dimensional model of detail from a requirement specification to the model and designer documentation. The technology of creating a three-dimensional model details the type of housing in the synchronous design environment of modern CAD Solid Edge. The features of creating and editing a three-dimensional model of the part and its elements are given in detail, taking into account the features of technological processes of forming cutting. It is considered as by means of managing 3d-розмірів and geometrical connections between 3d-об'єктами exact control of geometry is realized in synchronous technology. In Solid Edge with synchronous technology structural elements are independent and kept not in the tree of model, but in a navigator. Computer imitation models allow operatively to investigate and pick up the optimal modes and parameters of technological process, that promotes efficiency, exactness and quality of production considerably. Modern technologies not only simplify work to the engineer-designer, but also considerably cut prime cost production. A comparative analysis of the design in synchronous and parametric environments with an explanation of the advantages and disadvantages. Synchronous technology unites in itself advantages of self-reactance and direct design, and eliminates the lacks of both approaches.
Development of technology and comparative analysis of creating three-dimensional models in modern CAD systems taking into account the formation processes by cutting
Keywords: комп'ютерна модель; алгоритм; параметричне проектування; синхронне проектування; computer model; algorithm; the parametric design; synchronous design